Práticas pedagógicas docentes de matemática : relações com o ensino e aprendizagem no ensino médio regular de Belém do Pará - Maia, Anderson Madson Oliveira (2023)
ABSTRACT: This study aims to analyze the influence of pedagogical practice on the teaching-learning process developed by Mathematics teachers with regular high school students in public schools of Belém do Pará, whose object of study consists of developing how teachers perceive the relationship of their Pedagogical practices regarding student learning of Math in school teaching. In the specific objectives, we analyze the conceptions that guide such pedagogical practices developed in schools; I discuss, based on the perceptions of the research interlocutors, the pedagogical practices used for learning in Mathematics teaching; I reflect on the relationships between these practices and learning in the teaching of Mathematics education in student schools. The research methodology was guided by the demands of the historical dialectical method, in a qualitative nature, whose data collections were bibliographical and field research, as a technique, the interview and data treatment took place through content analysis. As the main result found, I emphasize that the teaching practices influence the interpretive and critical-dialectical conceptions, which defend a contextualized teaching, which dialogues with the particularities of the Pará and Amazon, revealing the potential of Mathematics education, as a social practice that, effectively , expands the possibilities of a more humanized teaching of the subject and connected to the needs of students and, therefore, of society, understanding Mathematics as a science in motion, advancing beyond traditional teaching practices. I believe that this research contributes to the investment in pedagogical practices, which involve critical thinking, when they are coated with meanings, capable of motivating students to apprehend concepts and contents applied to the student's social reality.